Low cost piezoresistive pressure sensor matrix for pressure ulcer prevention and management - Fajingbesi, Fawwaz Eniola; Azman, Amelia Wong; Ahmad, Zuraida; Olanrewaju, Rashidah Funke; Ibrahimy, Muhammad Ibn; Mohd. Mustafah, Yasir (IEEE, 2020)
Combating Pressure Ulcer (PU) prevalence have proven to be time and cost-intensive. Higher risk of morbidity is seen from slight negligence with immobilized subjects. Best PU prevention mostly revolves around constant pressure unloading once above 32mmHg which is detrimental on the blood capillaries and surrounding tissues. Thus, real-time pressure monitoring and unloading protocol are highly favored with PU at-risk patients. It may either be manual (Clinician/Caregivers following established protocols from PU Risk Assesment Tools (RATs)) or semi- to fully automated systems incorporating pressure monitoring devices. These existing pressure sensing systems are either rigid and or couldn’t support full-time integration without increasing mechanical stress and shear force imposed upon contact interface due to their slippery polymeric surface material (PET/PVC/PDMS/PI etc) used for sensor packaging to increase flexibility and conformity on diverse surface shapes. They have similarly compromised on breathability and hydrophilic material selection conducive in pressure ulcer prevention and management. Although there have been results from recent research producing fully textile sensors, their cost and instability are still on the high side. Thus, this paper introduces rapid prototyping compatible low-cost PU prevention and management friendly textile pressure sensing device compatible with existing actuation or electrical stimulation system, which will relay in order to allow targeted pressure relief according to feedbacks from the pressure monitoring system. A prototype Flexi-semi breathable, piezoresistive pressure sensor matrix has been fabricated based on a polymeric foil (polyolefins) impregnated with carbon black (Velostat) sandwich between a pair of ultra-thin copper-lined bamboo fabric. With an overall height of about 800 µm, the surface area of 210 * 297 mm, a total of 140 pressure sensor nodes are enclosed evenly to measure pressure directly, without any deformation elements, such as in cantilever or a deformation membrane.